The role of peripheral retinal angiography in the diagnosis of adult Coats’ disease based on a case report - Turczyńska, Monika; Brydak-Godowska, Joanna (Klinika Oczna / Acta Ophthalmologica Polonica, 2020)
The paper presents a case of a 58-year-old woman with hypertension, who suffered unilateral visual loss due to vitreous hemorrhage in the right eye. Clinical examination, fluorescein and indocyanine green angiography and ultrasonography were performed. Following vitreous hemorrhage resorption, fundoscopy showed atypical retinal vessels located temporally to the macula. Fluorescein and indocyanine green angiograms confirmed atypical vessels in the peripheral retina. Diagnosis of adult onset Coats’ disease was made for the atypical lesions and treatment with retinal laser photocoagulation was administered to prevent further hemorrhage. Coats’ disease, most commonly seen in male children, is rarely diagnosed in the adult female population. In adults, the course of the disease tends to be less severe than in children. When investigating the cause of vitreous hemorrhage, we have to take pathological neovascularization typical for Coat’s disease into consideration as a differential diagnosis. Fundoscopy of the peripheral retina is an examination that can aid in diagnosis after absorption of vitreous hemorrhage. Wide-field angiography confirms the diagnosis, enables precise localization of pathological vessels and their activity, and helps determine treatment effectiveness.